Evaluating emergency physicians' knowledge, attitudes, and experiences of FARC ex‐combatants: A pilot study of Colombia's emergency medicine teaching hospitals - Christopher W. Reynolds; Leonar G. Aguiar; Katelyn Moretti; Andres Duarte; Fabián Andrés Rosas Romero; Andres Patiño; Adrienne Fricke; Virginia Zarama; Atilio Moreno; Heidy Carranza; Christian Arbelaez (Journal of the American College of Emergency Physicians Open, 2020)
Abstract Objectives In the 2016 Peace Accord with the Fuerzas Armadas Revolucionarias de Colombia (FARC), Colombia promised to reincorporate 14,000 ex‐combatants into the healthcare system. However, FARC ex‐combatants have faced significant challenges in receiving healthcare, and little is known about physicians’ abilities to address this population's healthcare needs. Methods An electronic questionnaire sent to the Colombian Emergency Medicine professional society and teaching hospitals assessed physicians’ knowledge, attitudes, and experiences with the FARC ex‐combatant reincorporation process. Results Among 53 participants, most were male (60.4%), and ∼25% were affected by the FARC conflict (22.6%). Overall knowledge of FARC reincorporation was low, with nearly two‐thirds of participants (61.6%) scoring in the lowest category. Attitudes around ex‐combatants showed low bias. Few physicians received training about reincorporation (7.5%), but 83% indicated they would like such training. Twenty‐two participants (41.5%) had identified a patient as an ex‐combatant in the healthcare setting. Higher knowledge scores were significantly correlated with training about reincorporation (r = 0.354, n = 53, P = 0.015), and experience identifying patients as ex‐combatants (r = 0.356, n = 47, P = 0.014). Conclusion Findings suggested high interest in training and low knowledge of the reincorporation process. Most physicians had low bias, frequent experiences with ex‐combatants, and cared for these patients when they self‐identify. The emergency department (ED) serves as an entrance into healthcare for this population and a potential setting for interventions to improve care delivery, especially those related to mental healthcare. Future studies could evaluate effects of care delivery following training on ex‐combatant healthcare reintegration.